Financial Anxiety, Physiological Arousal, and Planning Intention - John Grable; Wookjae Heo; Abed Rabbani (Journal of Financial Therapy, 2015)
Results from this exploratory clinical study indicate that financial anxiety—holding an unhealthy attitude about one’s financial situation—and physiological arousal—the physical precursor to behavior—play important roles in shaping consumer intention to engage in future financial planning activity. Findings suggest that those who are most likely to engage the services of a financial adviser exhibit low levels of financial anxiety and moderate to high levels of physiological arousal. The least likely to seek the help of a financial adviser are those who exhibit high financial anxiety and low physiological arousal. Results support findings documented in the literature that high anxiety levels often lead to a form of self-imposed helplessness. In order to move those experiencing financial anxiety towards financial solutions, financial advisers ought to take steps to simultaneously reduce financial stressors and stimulate arousal as a way to promote behavioral change and help seeking.
Keywords: Stress; Anxiety; Financial Stress; Psychophysiological; Economics